Trilhares que ensinam: incursões em experiências formativas portuguesas para ressignificação de modelos formativos brasileiros - Pessôa, Lilian Corrêia (2015)
Starting from the questioning that rose from our experience as a researcher, while giving training to curriculum coordinators in one of the teaching directories of the State of São Paulo, this research aims to find the structure needed to promote the increasing value of formative models that might promote the professional development of the participants. Considering the common use of Portuguese literature for teacher training in Brasil, it was established an exchange with Portuguese trainers that had worked in relevant training in their own country. The theoretical framework was built using Henri Wallon contributions, mainly over group creation and the relationships with the environment and with the others, but also with the parts that compose the teaching-learning process, where it stood out the contagious nature of emotion as a way to facilitate the engagement of the training professionals. For the issues concerning the training processes I used leading authors like Marcelo, Gatti, André, Barreto, Formosinho, Roldão, Canário and et al. The collected data came originally from eight unstructured interviews done live with Portuguese trainers that work in the Aveiro, Minho and Lisboa universities and also in the Instituto Politécnico de Lisboa. From those interviews it was established eight guidelines that were used to perform our analysis. Those guidelines are: 1 - School and university relations; 2 - Contagious" effects of training; 3 - Training and research; 4 Trainer of trainers; 5 - Cooperative work; 6 - Training perspectives; 7 - Training strategies; 8 - Execution and professional experience context. The research results pointing towards: the need to build a training theory that can be used to base training actions; the importance of establishing clear criteria for the trainer selection, changing the notion that a good teacher is automatically a good trainer; developing a cooperative work as a way to break the established hierarchy in training today, but also involving all the players, and promoting the shared responsibility in decision making; the importance to create a training that, because of the value the theoretical dimension of training, can contribute to the resolution of specific situations in the educational context of the teacher, and so each group in training can have specific training actions, because each context (environment, the others agents and the situations created by the interaction) is different. And to conclude, it presents, as a possibility, the creation of research models that will allow to discover the best profile for a training teacher, and also the knowhow that should be expected, specially concerning: training strategies, adult education, creation and management of intervention cooperative projects, and practice analysis